2017
DOI: 10.11114/ijsss.v5i5.2360
|View full text |Cite
|
Sign up to set email alerts
|

Prayer Determination toward Employees Performance

Abstract: Prayer is a consequence for person who belief to God as their duty by performing in five times a day. Those are dawn Dzuhur, Ashar, Maghrib and sobs Prayer is the pillars of Muslim, "whoever does the direction, they has heighten their religion, whoever leave means has moved down theirs. Prayer will bring positive impact to performance of human if there is good process that followed and done constantly.According to Rais (1998:60) a good way in Prayer could give good charity to Muslims itself while if not, so t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Lukaski et al [68, 69] suggested that high-dose and long-term Cr(III) supplementation may adversely affect Fe metabolism in adults. Furthermore, several studies also showed an association between between iron metabolism and diabetes [5, 8, 9, 70]. One of the proposed mechanisms is oxidative stress induced by increased iron deposition in the liver and β cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lukaski et al [68, 69] suggested that high-dose and long-term Cr(III) supplementation may adversely affect Fe metabolism in adults. Furthermore, several studies also showed an association between between iron metabolism and diabetes [5, 8, 9, 70]. One of the proposed mechanisms is oxidative stress induced by increased iron deposition in the liver and β cells.…”
Section: Discussionmentioning
confidence: 99%
“…Increased Fe accumulation influences insulin synthesis and secretion by pancreatic β cells. Fe accumulation in the liver may lead to insulin resistance by interfering with the insulin capacity to inhibit hepatic glucose production [59].…”
Section: Introductionmentioning
confidence: 99%
“…It is an obligation imposed on every mukallaf. Lesmana, Isnanto, & Widianto, (2016); Ridho (2015); Wibisono & Hood, (2015) explains that shalat is a major obligation for every Muslim. This worship must be performed everyday and cannot be delegated to others.…”
Section: Al-ta'lim Journal 25 (1) 2018 (45-55)mentioning
confidence: 99%
“…Ridho 2015; Wibisono & Hood (2015) proposes that shalat is an act initiated by the takbiratul ihram and ended by salam. Shalat also has physical and spiritual benefits.…”
Section: Al-ta'lim Journal 25 (1) 2018 (45-55)mentioning
confidence: 99%
“…, Accompanied by school representative(Syed et al, 2018;Mirza, 2016), Privacy of building users(Lai & Lai, 2013;Olanrewaju & Aziz, 2015), Prohibited activities in Islam(Mahdi, 2016;Quoquab, 2016), Time of worship(Khan, 2017;Wibisono, 2017).…”
mentioning
confidence: 99%